Polycyrene-based Microbore Monolith Column Preparation for Separation of Alkylbenzene Using High Performance Liquid Chromatography - Aprilia Nur Tasfiyati; Wigang Solandjari; Elvina Dhiatul Iftitah; Akhmad Sabarudin (Natural B, Journal of Health and Environmental Sciences, 2015)
In this study, polystyrene-based monolith was developed as reversed phase column in high performance liquid chromatography (HPLC) for separation of small molecule sample (alkylbenzene). Polystyrene-based monolithic column was prepared in microbore silicosteel column (100 x 1.02 mm i.d.) by in-situ polymerization reaction using styrene as monomer, divinylbenzene as crosslinker, porogenic solvents, with the presence of radical initiator 2,2’-azobis(isobutyronitrile). The morphology of the monolithic column was studied by SEM. The properties of the monolithic column, such as permeability, mechanical stability, binding capacity and pore size distribution, were characterized in detail. From the characterization results of 9 monolith variation, monolith PS-DVB with %T 30, %C 50, using toluene:1-decanol (3:7 v/v) as porogenic solvent was found to be the ideal composition and gave the best separation of alkylbenzene. It has theoretical plate value (N) of 17260/m column, also has relatively equal proportion of flow-through pore and mesopores (47% and 44% respectively). The performance of monolithic column was also compared with commercially available monolithic column Proswift RP-4H. PS-DVB monolith prepared in this study shown its superiority over commercial one.